REKAYASA PERANGKAT LUNAK SISTEM INFORMASI MONOGRAFI DESA BERBASIS WEB PADA PEMERINTAHAN DESA SUKADALEM - Masum Masum; Suefi Ajistama (LPPM Unbaja, 2020)
Village Government representing the interaction process alternating pattern continued between the two entities are inseparable village officials and individual citizens of the village. Organization structure of village government as established by the citizens of the village in order to meet the needs facility public services at the village level. Fulfillment of public service at village level, one of which is the fulfillment of a need for information about the village or village is often called monographs. Monograph of the village is recorded activities and information about the situation in rural areas, which describes among other things limits owned, local geographic conditions, population, livelihood or occupation, religion, number and amount of Neighborhood Residents Pillars, so that citizens can knowing the condition and potential of the village.Sukadalem Village is one of the villages located in Waringin Kurung district, Serang regency, Banten province. Sukadalem village like other villages in Indonesia, also has a village monograph information systems. Monograph information systems owned by rural villages still use the board Sukadalem whiteboard is attached to the wall in the village office, this causes the data processing is less effective monographs and the information was not up to date, it is also difficult for people because people have come to the village office just to see information about the village. The problem of the above issues it is necessary to build a village monograph information system that is online, so they can streamline data processing village monograph.